The Elites’ Detachment from the People and People’s Detachment from the Constitution - Pinelli Cesare (Baltic Journal of Law & Politics)
The contribution argues that the issue of popular detachment from the constitution should draw attention from constitutionalists far more than the populist mantra of the elites’ detachment from the people. To that end, the article goes back to the establishment of a constitutional tradition in continental Europe, namely of a legitimacy relying on a permanent correspondence of popular values with constitutional principles, and explores the reasons of its crisis, frequently perceived as a ‘constitutional retrogression’. The author includes both the waning of a long-sighted perspective on politics and the rise of a communicative system, which challenge constitutional democracies on cognitive grounds, with consequences that go far beyond the populist narrative.